Pengaruh Good Corporate Governance, Ukuran Perusahaan, Pertumbuhan Penjualan, Return on Asset Terhadap Penghindaran Pajak pada Perusahaan yang Terdaftar dalam Jakarta Islamic Index Tahun 2018-2022 - Prayogo, Mas Daud; Desmiza, Desmiza (Efektor, 2024)
This research aims to examine the effect of good corporate governance as proxied by institutional ownership, independent commissioners, audit committee, company size, sales growth and return on assets on tax avoidance as proxied by the cash effective tax rate in companies listed in the 2018 Jakarta Islamic Index. -2022. Annual financial reports are used as a secondary data source in this research. Company financial report data for the 2018-2022 period was collected using the documentation method via the Indonesia Stock Exchange (BEI) website. The population in this study was 41 companies and the sample in this study was 16 companies selected using the purposive sampling method. The data analysis technique used is panel data regression analysis to test the influence of the independent variable on the dependent variable. The results of this research show that institutional ownership and independent commissioners have a negative effect on tax avoidance. Then sales growth and return on assets have a positive effect on tax avoidance. Meanwhile, the audit committee and company size have no effect on tax avoidance. The Adjusted R Square value is 70.61 percent, meaning that the ability of the independent variable to explain the dependent variable is 70.61%, the remaining 29.39 percent is due to other variables not examined.